The Epidemic of Sexually Transmitted Diseases Under the Influence of COVID-19 in China - Yan, Xiangyu; Wang, Xuechun; Zhang, Xiangyu; Wang, Lei; Zhang, Bo; Jia, Zhongwei (Frontiers in Public Health, 2021)
Background: Prevention and control of HIV/AIDS and other sexually transmitted diseases (STDs) are major public health priorities in China, but are influenced by COVID-19’s epidemic. We aimed to quantitatively explore the impact of COVID-19’s epidemic and its control measures on five major STDs’ epidemic in China. Methods: Monthly number of newly reported cases of HIV/AIDS, hepatitis B and C, gonorrhea, and syphilis from January, 2010 to December, 2020 were extracted to establish ARIMA models. Each month’s absolute percentage error (APE) between actual value and model-predicted value of each STD was calculated to evaluate the influence of COVID-19’s epidemic on the STDs. Correlation analysis was conducted to explore COVID-19 case numbers and COVID-19 control measures’ correlations with case numbers and APEs of five STDs. Results: The actual number of five STDs in China was more than 50% lower than the predicted number in the early days of COVID-19 epidemic, especially in February. Among them, the actual number of cases of hepatitis C, gonorrhea and syphilis in February 2020 was more than 100% lower than the predicted number (APE was -102.3%, -109.0% and -100.4%, respectively). After the sharply declines of STDs’ reported cases in early 2020, the case numbers recovered quickly after March. The epidemic of STDs was negatively associated with COVID-19’s epidemic and its control measures (p<0.05). Conclusion: COVID-19 had a significant but temporary influence on STDs’ epidemic in China. STD services need to be improved to prevent the STDs from becoming a secluded corner in the shadow of COVID-19.